Assessing Spatial and Temporal Patterns of Observed Ground-level Ozone in China - Wan-Nan Wang (Nature Portfolio, 2017)
Abstract Elevated ground-level ozone (O3), which is an important aspect of air quality related to public health, has been causing increasing concern. This study investigated the spatiotemporal distribution of ground-level O3 concentrations in China using a dataset from the Chinese national air quality monitoring network during 2013–2015. This research analyzed the diurnal, monthly and yearly variation of O3 concentrations in both sparsely and densely populated regions. In particular, 6 major Chinese cities were selected to allow a discussion of variations in O3 levels in detail, Beijing, Chengdu, Guangzhou, Lanzhou, Shanghai, and Urumchi, located on both sides of the Heihe-Tengchong line. Data showed that the nationwide 3-year MDA8 of ground-level O3 was 80.26 μg/m3. Ground-level O3 concentrations exhibited monthly variability peaking in summer and reaching the lowest levels in winter. The diurnal cycle reached a minimum in morning and peaked in the afternoon. Yearly average O3 MDA8 concentrations in Beijing, Chengdu, Lanzhou, and Shanghai in 2015 increased 12%, 25%, 34%, 22%, respectively, when compared with those in 2013. Compared with World Health Organization O3 guidelines, Beijing, Chengdu, Guangzhou, and Shanghai suffered O3 pollution in excess of the 8-hour O3 standard for more than 30% of the days in 2013 to 2015.